Energy management in the newspaper production process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The print media has proven to be a powerfulcommunication medium on issues such as climate change, depletionof energy resources, use of renewable and conventional energysources and their impact on the quality of life of society, biodiversityand ecosystems, serving as a means of raising awareness.Additionally, the energy consumption of print media facilitiescontributes to these changes, as a result of greenhouse gas emissionsfrom the consumption of electricity in its newsroom processes and inthe printing of copies, in the case of paper newspapers. This papershows the results obtained from the analysis of the electric energyconsumption of a newspaper printing company obtained from anenergy audit. The results show that with measures on the airconditioning equipment systems, benefits are reflected as a betterredistribution of the energy matrix and a reduction in energyconsumption, which is reflected in the estimated energy efficiencyindexes based on the number of printed copies, employees andconstruction area.